Matrix mathematics : theory, facts, and formulas - Bernstein, Dennis S., 1954- (Princeton University Press, 2009)
Each chapter in this book describes relevant background theory followed by specialized results. Hundreds of identitites, inequalities, and matrix facts are stated clearly with cross references, citations to the literature, and illuminating remarks.